Evolução geomorfológica e palaeoambiental dos terraços da margem esquerda do alto rio Paraná - Guerreiro, Renato Lada [UNESP] (2011)
Terraces levels and sedimentary deposits of different ages and characteristics in the upper Paraná River has been associated as a paleohydrological and paleoenvironmental record by Quaternary paleoclimatic changes. The study area is located in northwest of Paraná State (Brazil), near to Querência do Norte city, left bank of upper Paraná river. Based on remote sensing data and fieldworks, including vibro-core drilling and outcrops description, was held the study área geomorphological subdivision and caracterization, with recognition of terraces associated of Parana and Ivaí rivers, current plains of both rivers, various formats ponds and inactive alluvial fans formed by streams that drain high land. Geomorphology, geology, absolute dating (OSL and 14C) and interpretation of proxy records data as continental sponges spicules, diatoms frustules and phytoliths allowed to reconstruct paleoenvironmental and paleoclimatic conditions. Dating showed ages of 150,900 ± 32,400 and 50,300 ± 7900 years BP to terraces; 26,900 ± 5,000 and 20,600 ± 4800 years BP to ponds; and 7,540 years BP to aluvial fan. The terraces of the study area were correlated with the geomorphological units Taquaruçu and Fazenda Boa Vista, in southeastern Mato Grosso do Sul State (Brazil), and Ivaí Terrace on the right bank of the lower Ivaí river. The terraces were interpreted as extensions of these units and products of the same Quaternary paleoenvironmental / paleoclimatic changes events. The presence of sponge spicules in lake sediments show that lotic environments were not associated with the ponds genesis and evolution. Gemmoscleres were identified corresponding to four sponges species: a) Dosilia pydanieli; b) Radiospongilla amazonensis c) Metania spinata; and d) Uruguaya corallioides, as well two genus of diatoms frustules: a) Pinnularia sp. and b) Eunotia sp., which enabled the interpretation of paleoenvironmental change. The terraces degradation and ...